PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PENERBANG PADA PT. GARUDA INDONESIA (PERSERO) - Evaf Maulina; IG. P. Mastra; Dewi Dyah W (JURNAL MITRA MANAJEMEN, 2020)
ABSTRACT EFFECT OF INDIVIDUAL CHARACTERISTICS AND PERFORMANCE CHARACTERISTICS OF WORK IN AVIATOR. GARUDA INDONESIA (PERSERO) Leaders are required to understand the behavior of individuals. The difference is reflected in the individual goals must be considered by the company to be met in order to align with corporate goals. Characteristics are taken in the work environment will have an effect on performance, purpose of this study to determine the effect of individual characteristics on the performance of aviators at PT. Garuda Indonesia (Persero). To determine the effect of job characteristics on aviator performance at PT. Garuda Indonesia (Persero). To determine the effect of individual characteristics and the characteristics of the work jointly on the performance of aviators at PT. Garuda Indonesia (Persero). There is the influence of individual characteristics on the performance of aviators. Proven tcount obtained for variable X1 (individual characteristics) amounted to 5,001, while the value for n = 47 ttable amounted to 2,010. So 5,001 > 2,010, it can be concluded that in partial Individual characteristics (X1) does have a positive effect on the performance of aviators (Y). There is the influence of job characteristics on the performance of aviators. Proven tcount obtained for variable X2 (job characteristics) amounted to 4,476, while the value for n = 47 ttable amounted to 2,010. So 4,476 > 2,010, it can be concluded that in partial job characteristics (X2) does have a positive effect on the performance of aviators (Y). There is the influence of individual characteristics and job characteristics jointly on the performance of aviators. ANOVA or F value of these calculations in to a value of 26,674 which is greater than 2.80 Ftable Thus it is clear that the calculation of F > F or 26,674 > 2.80 with a significant level of 0.000 for 0.000 < 0.05, it can be said variable characteristic individual (X1) and job characteristics variables (X2) jointly affect the aviators performance variable (Y). While the value of R Square of 0.740 means that the characteristics of the individual and job characteristics have an influence on the performance by 74 % while the remaining pilots by 26% with the effect of other factors that were not studied by the authors in this study. Keywords : individual characteristics, job characteristics and performance of aviators